Bitterness : perception, chemistry and food processing - Aliani, Michel; Eskin, N. A. M. (John Wiley & Sons, Inc., 2017)
"Bitterness is one of the most interesting and least studied/understood of all the human tastes. It produces aversive reactions because it was originally associated with the plant source being poisonous. In fact, it was considered a defence mechanism for avoiding the ingestion of such harmful substances so that early human survival was based on the knowledge and ability to discriminate between edible plants particularly those with potentially harmful effects. With the advent of modern technology our understanding of bitterness is far more sophisticated and that we now know that not all bitter compounds are poisonous. In fact there are many foods in which bitterness is quite acceptable such as in some cheeses and beverages. In this book we have attempted to provide a comprehensive review of bitterness, from the novel genes in humans responsible for the expression of bitterness to methods used to remove or reduce bitterness in functional foods and nutraceuticals. The book is organized into five sections. The first section covers the biology of bitterness perception with Chapter 1 discussing the biochemistry of the 25 human bitter taste receptors of the TAS2R gene family. Chapter 2 examines the physiological aspects of bitterness while Chapter 3 discusses human bitterness from an evolutionary perspective"- Resumé vydavatel
Keywords: potraviny; foodstuffs; hořkost; kolektivní monografie; elektronické knihy; collective monographs; electronic books